VD_FINDINFO Plainte / 2024 / 17 vom 18. Juni 2024 - VD Tribunal cantonal (2024)
GAGE IMMOBILIER, POURSUITE EN RÉALISATION DE GAGE, PROCÉDURE D'ESTIMATION, EXPERTISE | 9 al. 1 ORFI, 9 al. 2 ORFI, 9 ORFI